CT-SCAN EXAMINATION TECHNIQUE FOR PARANASAL SINUSES WITH CHRONIC RHINOSINUSITIS CLINICAL AT IN RADIOLOGY INSTALATION AWAL BROS PEKANBARU HOSPITAL - Putri Melati; Ahmad Darbi; Aisha Rahma (LPPM Universitas Awal Bros, 2026)
Background: Chronic rhinosinusitis (CRS) is a chronic inflammation of the nasal cavity and paranasal sinuses lasting more than 12 weeks and can be caused by various factors, one of which is anatomical variations of the paranasal sinuses. Computed Tomography (CT) Scan is an imaging modality that is capable of providing detailed anatomical visualization of the nasal cavity and paranasal sinuses, including the ostiomeatal complex, anatomical abnormalities, and pathological changes within the sinuses. In clinical practice, CT scan examination of the paranasal sinuses must be adjusted to the patient’s condition and the procedures implemented in healthcare facilities. This study aims to determine the CT scan examination technique of the paranasal sinuses in cases of chronic rhinosinusitis at the Radiology Department of Awal Bros A. Yani Hospital. Methods: This study used a descriptive method with a case study approach. Data were collected through observation, documentation, and interviews with radiographers. The study subject was a patient with clinical chronic rhinosinusitis undergoing a CT scan examination of the paranasal sinuses. Results: The examination was performed without special preparation, except for the removal of metallic objects in the examination area. The patient was positioned supine with a head-first position and arms placed alongside the body. The scan range included from the frontal sinus to the maxillary sinus. The examination used parameters of 120 kV and 175 mA with a 19.8 cm FOV. Image reconstruction was performed with a slice thickness of 3 mm in axial, coronal, and sagittal planes. Radiation protection optimization was carried out by adjusting examination parameters according to clinical needs. The CT scan technique of the paranasal sinuses in cases of chronic rhinosinusitis at the Radiology Department of Awal Bros A. Yani Hospital is performed through stages of preparation, positioning, scanning, image reconstruction, and radiation protection optimization according to examination requirements.